Senior Citizens Leaders Transforming the Subculture of the Day Care Center through Physical Activity - Murillo-Campos, Edgar (2016)
Purpose: The main objective of this study was to analyze the impact that leadership has when exercised by senior citizens as they modify healthy lifestyles through physical exercise. Methodology: It featured 36 senior-citizen participants of the Senior Day Care Center of Belén (CDAMB, by its initials in Spanish), seven men aged between 65 and 91 years old (x =79.43 years old, ± 8.02) and twenty-nine women with ages between 65 and 100 years old (x = 85 years ± 9.38). Based on interviews to CDAMB administrators, three persons were selected to participate in a training program in the field of promoting healthy lifestyles. This study collected data using the International Questionnaire for Physical Activity or IPAQ, long form version 8, Questionnaire to Evaluate perceived Physical Capacity (CFP, by its initials in Spanish), Confidence in the Physical Self-Presentation (CAPF, by its initials in Spanish) questionnaire and a focus group interview. Procedure: Once three leaders were identified, training was carried out in the field of promoting healthy lifestyles; subsequently, a pretest was conducted to assess the basic fitness and emotional condition of all individuals involved. From then on, the three leaders created different activities according to the training received. After eight weeks of intervention, a post-test was carried out. The data from IPAQ, CFP and CAPF were analyzed using t-student tests for replicated measures. The focus group provided subjective information on the experience of senior citizens. Results: Trends towards improvement in CFP and CAPF were recorded. Concerning the variable “physical activity during leisure time” (physical exercise, recreation and use of leisure time), positive changes, statistically significant, were recorded. In general, positive opinions regarding the intervention made by leading people were collected. Findings: Training older adults as leaders in promoting healthy lifestyles represents an innovation in the modification of the CDAMB subculture. Physical activity takes on a key role for this age group, especially during leisure time, as well as, a very positive psychosocial atmosphere is rescued in the dynamics of the Center.